Research Trends for Gifted Care in the Hashemite Kingdom of Jordan: A Systematic Review of the Literature 2014-2024 - Rababah, Ahmad (Jordan Journal of Educational Sciences, 2025)
ABSTRACT Objectives: The study aimed to explore research trends in the field of gifted care, and to reveal the most commonly used research practices (methodology and procedures) in Jordan for the period 2014-2024. Methodology: The study followed the descriptive analytical approach, and used the (PRISMA) appendix as a tool to limit and include studies. It included 177 studies. Results: The results revealed a set of research trends arranged in descending order as follows: personal and social characteristics of the gifted at a rate of 15.82%, assessment at a rate of 14.69%, educational and pedagogical practices at a rate of 14.12%, thinking skills at a rate of 13.56%, the effectiveness of various strategies and programs at a rate of 12.99%, mental health and social adaptation at a rate of 10.73%, detection and identification services at a rate of 6.21%, implicit theories among stakeholders at a rate of 5.65%, developmental perceptions at a rate of 3.95%, and some other axes at a rate of 2.26%. It also revealed that the quantitative approach and tools are the most commonly used, and gifted students are the most targeted samples. Conclusion: The study recommends the necessity of using more in-depth research methods in studying phenomena, using qualitative tools to collect data, and avoiding stereotypes in scientific research. Keywords: Systematic review, Gifted, Research Trends. Keywords: Systematic review, gifted, research Trends.